Penerapan Permainan Tradisional Gobag Sodor Untuk Meningkatkan Kemampuan Motorik Kasar Anak Kelas III SDN 2 Tuguraja Tasikmalaya - Nunung Nunung; Agus Ahmad Wakih; Deni Chandra (Lembaga Pengembangan Kinerja Dosen, 2023)
Gross motor development is very important for children's growth and development. The purpose of this study was to describe the improvement of children's gross motor skills in PJOK learning in grade III SDN 2 Tuguraja through the application of traditional gobag sodor games. This research method is Classroom Action Research (PTK). Data collection techniques through observation, tests and documentation. The subjects of this study were grade III students of SDN 2 Tuguraja with a total of 26 students. The results showed that there was an increase in children's gross motor skills through the application of traditional gobag sodor games. The increase can be seen from the results of the study; pre-cycle with an average gain of 70.67, namely 11 students (42.30%) completed KKM and 15 students (57.70%) did not complete KKM, after the first cycle action, the average score was 78.36, namely 14 students (53.85%) completed KKM and 12 students (46.15%) did not complete KKM, then in cycle II saw a significant increase, the average score acquisition was 86.53 showing 22 students (84.62%) completed KKM and 4 students (15.38%) were incomplete KKM. Based on the results of research for 2 cycles, it can be concluded that through the application of traditional gobag sodor games can improve gross motor skills of grade III SDN 2 Tuguraja students, especially in balanced and agile movements.